Assessment of Nutritional Status in the Critically Ill - Narayan, Shiva K (Indian J Crit Care Med, 2020)
How to cite this article: Narayan SK, Gudivada KK, Krishna B. Assessment of Nutritional Status in the Critically Ill. Indian J Crit Care Med 2020;24(Suppl 4):S152–S156.